2021
DOI: 10.3762/bjnano.12.3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different silica coatings on the toxicity of upconversion nanoparticles on RAW 264.7 macrophage cells

Abstract: Upconversion nanoparticles (UCNPs), consisting of NaYF4 doped with 18% Yb and 2% Er, were coated with microporous silica shells with thickness values of 7 ± 2 and 21 ± 3 nm. Subsequently, the negatively charged particles were functionalized with N-(6-aminohexyl)-3-aminopropyltrimethoxysilane (AHAPS), which provide a positive charge to the nanoparticle surface. Inductively coupled plasma optical emission spectrometry (ICP-OES) measurements revealed that, over the course of 24h, particles with thicker shells rel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 80 publications
3
6
0
Order By: Relevance
“…6 b). This is in accordance with the lower toxicity of UCNPs with thicker silica shells as compared to those with thinner silica shells previously reported by Kembuan et al 12 for macrophages (RAW 264.7 cells).
Figure 6 Viability of HaCaT cells exposed to ( a ) UC-SiO 2 -thick and UC-SiO 2 -thin for 24 h and 48 h; and ( b ) UC-bare-20 (BF 4 ) and UC-SiO 2 -thick after 72 h of aging in di-H 2 O and DMEM.
…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…6 b). This is in accordance with the lower toxicity of UCNPs with thicker silica shells as compared to those with thinner silica shells previously reported by Kembuan et al 12 for macrophages (RAW 264.7 cells).
Figure 6 Viability of HaCaT cells exposed to ( a ) UC-SiO 2 -thick and UC-SiO 2 -thin for 24 h and 48 h; and ( b ) UC-bare-20 (BF 4 ) and UC-SiO 2 -thick after 72 h of aging in di-H 2 O and DMEM.
…”
Section: Resultssupporting
confidence: 92%
“…Despite the large number of advantages of UCNPs and possible biomedical applications, concerns about their biosafety and potential adverse effects have been raised 12 , 13 , as the dissolution of NaYF 4 UCNPs in aqueous media can result in the release of fluoride and lanthanide ions which can induce cytotoxicity in biological systems 14 18 , particularly under high dilution conditions in aqueous media 11 , 14 , 15 , 19 . Surface modification with various ligands has been used not only to tune the dispersibility and colloidal stability of NaYF 4 UCNPs, but also to reduce their dissolution in aqueous environments, as the release of fluoride and lanthanide ions may induce cytotoxicity in biological systems 14 18 , 20 .…”
Section: Introductionmentioning
confidence: 99%
“…The viability assays based on dehydrogenase detection (MTT and MTS assay) indicated that UC n induced greater effects than UC@CB [7]. Higher cytotoxicity was also reported previously for uncoated UCNPs when compared to silica-coated ones in RAW 264.7 cells and was attributed to higher internalization of negatively charged uncoated UCNPs [25]. Similarly, our results also indicate that a particle concentration up to 12.5 µg/mL does not lead to a critical cell line viability.…”
Section: Discussionsupporting
confidence: 86%
“…Nevertheless, cytotoxicity on HeLa and RAW 267.4 depended on the UCNPs tested. UC n and UC@CB [7] showed moderate and low cytotoxicity, respectively, in macrophages in a similar trend to that observed by Kembuan et al [25], indicating the enhancement of the biocompatibility of UCNPs nanoparticles upon cucurbit [7]uril coating. UC n and UC@CB [7] showed very low cytotoxicity on HeLa; see Figure 3.…”
Section: Cytotoxicitysupporting
confidence: 87%
See 1 more Smart Citation